Physical-chemical properties modiﬁcation of hermetia illucens larvae oil and diesel fuel for the internal combustion engines application - Yusaf, Talal F.; Mohd Kamal, Kamarulzaman; Abdul Adam, Abdullah; Sakinah, Muhamad Hisham; Ramasamy, Devarajan; Kadirgama, Kumaran; Samykano, Mahendran; Subramaniam, Sivaraos (MDPI, 2022)
The use of insects as a biofuel feedstock has received limited research, and little is known about the fuel characteristics of insect biofuel. Fuel properties characterization can guide researchers focused on renewable fuel for the internal combustion engine. Therefore, this investigation focused on the physical-chemical properties modification of Hermetia illucens larvae oil (HILO) and diesel fuel blends, which could highly become an alternative renewable fuel. Five test fuel blends of HILO and diesel fuel were prepared at 0%, 25%, 50%, 75%, and 100% on a volume basis. Fuel properties such as chemical composition, density, viscosity, heating value, cetane number, and flash point of the test fuel blends were analyzed and compared to the diesel fuel. The main physical-chemical properties of HILO-diesel fuel blends were determined following the ASTM standards. Based on the results, the density, viscosity, cetane number, and flash point of the diesel fuel-HILO fuel blends were increased by 11.28%, 740.30%, 16.92%, and 86.67%, respectively, with the addition of HILO, except for the heating value reduced by 13.66%.